Lung Adenocarcinoma Patient Harboring EGFR-KDD Achieve Durable Response to Afatinib: A Case Report and Literature Review - Zhao, Lingling; Wang, Zhen; Du, Haiwei; Chen, Songan; Wang, Pingli (Frontiers in Oncology, 2021)
The rapid development of epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitors (TKIs) have revolutionized the treatment of patients with advanced or metastatic non-small cell lung cancer (NSCLC) harboring EGFR mutations including but not limited to exon 19 deletions and point mutation L858R in exon 21. However, the efficacy of EGFR-TKIs in patients with rare mutations, such as EGFR-kinase domain duplication (KDD), remains elusive. EGFR-KDD often results from in-frame tandem duplication of EGFR exons 18-25, causing subsequent constitutive activation of EGFR signaling. Several case reports have revealed the efficacies of EGFR-TKIs in advanced lung adenocarcinoma (LUAD) with EGFR-KDD but yielded variable antitumor responses. In the present study, we report a 61-year-old male patient diagnosed with T1N3M0 (stage IIIB) LUAD harboring EGFR-KDD involving exons 18-25. He was treated with Afatinib and achieved partial response (PR) with a progression-free survival (PFS) of 12 months and counting. Our work, confirming EGFR-KDD as an oncogenic driver and therapeutic target, provides clinical evidence to administer EGFR-TKIs in advanced LUAD patients harboring EGFR-KDD.